Special Focus Introduction: Literary Walks, Slow Travel, and Eco-Awareness in Contemporary Literature - Peter Arnds (Studies in 20th & 21st Century Literature, 2020)
Introduction to special focus on Literary Walks, Slow Travel, and Eco-Awareness in Contemporary Literature
Keywords: walking; slow travel; ecocriticism; literature; cycling